2016
DOI: 10.3892/mmr.2016.5553
|View full text |Cite
|
Sign up to set email alerts
|

CIP2A regulates proliferation and apoptosis of multiple myeloma cells

Abstract: Multiple myeloma (MM) is one of the most common causes of mortality from hematological malignancy in China. Recent studies have demonstrated that cancerous inhibitor of protein phosphatase 2A (CIP2A) may exhibit a role in promoting the growth of cancer; however, the function of CIP2A in MM remains unknown. In the present study, the expression and molecular mechanism underlying the effects of CIP2A in patients with MM and in MM cell lines were elucidated. Firstly, the expression of CIP2A was detected in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…CIP2A, also known as KIAA1524 and p90, is implicated as a human oncoprotein that promotes the stability of c-Myc protein and inhibits the degradation of c-Myc by inhibiting the protein phosphatase 2A-mediated dephosphorylation of Myc at Ser 62 ( 28 ). A number of studies have documented that CIP2A serves an important role in cell proliferation ( 29 ), transformation ( 30 ), drug resistance ( 31 ) and maintenance of a malignant cellular phenotype ( 32 ). Furthermore, CIP2A status was a significant prognostic factor for patients with non-small cell carcinoma, and CIP2A protein expression levels were revealed to be overexpressed in human lung cancer samples and associated with poor survival rates ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…CIP2A, also known as KIAA1524 and p90, is implicated as a human oncoprotein that promotes the stability of c-Myc protein and inhibits the degradation of c-Myc by inhibiting the protein phosphatase 2A-mediated dephosphorylation of Myc at Ser 62 ( 28 ). A number of studies have documented that CIP2A serves an important role in cell proliferation ( 29 ), transformation ( 30 ), drug resistance ( 31 ) and maintenance of a malignant cellular phenotype ( 32 ). Furthermore, CIP2A status was a significant prognostic factor for patients with non-small cell carcinoma, and CIP2A protein expression levels were revealed to be overexpressed in human lung cancer samples and associated with poor survival rates ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that CIP2A overexpression is associated with poor survival in patients with solid tumors and may serve as a predictive factor of poor prognosis. 10,15,25 Preclinical in vitro and in vivo studies have shown that CIP2A may regulate the proliferation, senescence, and apoptosis of multiple cancer cells [26][27][28] and contribute to resistance to chemotherapy such as cisplatin or docetaxel in solid tumors. [29][30][31] Therefore, CIP2A inhibition may serve as a promising modality to overcome chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…miR-518b has been deemed a tumor suppressor in carcinogenesis, as demonstrated by the observation that downregulation of miR-518b has frequently been detected in esophageal squamous cell carcinoma ( 17 ) and chondrosarcoma ( 18 ). In a recent study, a miRNA microarray demonstrated that miR-518b, which targets PDGFRB, is downregulated in microvascular proliferation, which may be the mechanism underlying the high expression of PDGFRB in GBM microvascular proliferation ( 19 ). The present study demonstrated that the expression of miR-518b was reduced in GBM tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…PDGFRB, which is a cell-surface tyrosine kinase receptor, is an important target for anticancer therapeutics ( 19 , 21 ). It has been reported that PDGFRB is an angiogenic factor, which is implicated in numerous cellular processes, including angiogenesis, proliferation and migration ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation